ANALISIS HADIS WANITA MEMAKAI PARFUM DAN KONTEKSTUALISASI KEKINIAN - Ahmad Ali Masyhuda (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2020)
The use of perfume is a common practice by both men and woman including when attending interests outside the home. However, in a hadith it is emphasized that women are prohibited from using perfume. Through this research the author tries to examine the hadith about the prohibition of perfume for women contextually. This research was carried out by searching and comparing similar traditions, considering the historical context and the purpose or maqashid of those traditions. From this study it can be concluded that the hadith that is understood contextually. Regarding the hadith about the prohibition of perfume for wome ifinterpreted textually becomes perfume is apart of bodily cleanliness, although in its use it is prohibited to overdo id